Kuliner “Timlo Solo” sebagai Bahan Ajar BIPA dalam Upaya Internasionalisasi Bahasa Indonesia - Kristin Setyawati; Imam Nurcahyono; Khansa Hafidza; Lina Juliasari; Khundaru Saddhono (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This article discusses the important role of teaching the Indonesian language for Foreign Speakers (BIPA) in supporting the internationalization of the language of Indonesia, with a focus on the use of the culinary material